Induction of Systemic Resistance in Cucumber by Hypovirulent Binucleate Rhizoctonia against Anthracnose Caused by Colletotrichum orbiculare - A. Muslim; Mitsuro Hyakumachi; Koji Kageyama (Tropical Life Sciences Research, 2019)
Treatment with hypovirulent binucleate Rhizoctonia (HBNR) isolates induced systemic resistance against anthracnose infected by Colletotrichum orbiculare in cucumber, as there were no direct interaction between HBNR and C. orbiculare. This is because of the different distances between HBNR and C. orbiculare, where the root was treated with HBNR isolate and C. orbiculare was challenged and inoculated in leaves or first true leaves were treated with HBNR isolate and C. orbiculare was challenged and inoculated in second true leaves. The use of barley grain inocula and culture filtrates of HBNR significantly reduced the lesion diameter compared to the control (p = 0.05). The total lesion diameter reduction by applying barley grain inoculum of HBNR L2, W1, W7, and Rhv7 was 28%, 44%, 39%, and 40%, respectively. Similar results was also observed in treatment using culture filtrate, and the reduction of total lesion diameter by culture filtrate of HBNR L2, W1, W7, and Rhv7 was 45%, 46%, 42%, and 48%, respectively. When cucumber root was treated with culture filtrates of HBNR, the lignin was enhanced at the pathogen penetration, which is spread along the epidermis tissue of cucumber hypocotyls. Peroxidase activity in hypocotyls in the treated cucumber plant with culture filtrates of HBNR significantly increased before and after inoculation of pathogens as compared to the control. Significant enhancement was also observed in the fast-moving anodic peroxidase isozymes in the treated plants with culture filtrates of HBNR. The results showed the elicitor(s) contained in culture filtrates in HBNR. The lignin deposition as well as the peroxidase activity is an important step to prevent systemically immunised plants from pathogen infection.